Revealing Surface Modifications of Potassium‐Fluoride‐Treated Cu(In, Ga)Se2: A Study of Material Structure, Chemistry, and Photovoltaic Performance. Issue 17 (6th July 2016) - Aguiar, Jeffery A.; Stokes, Adam; Jiang, Chun‐Sheng; Aoki, Toshihiro; Kotula, Paul G.; Patel, Maulik K.; Gorman, Brian; Al‐Jassim, Mowafak
Abstract : The effects of alkali post‐deposition treatments and device properties for polycrystalline thin film Cu(In, Ga)Se2 have been investigated. It is reported that these surface treatments lead to differences in interface chemistry and device properties. The behavior of defects in the space charge region as a function of different growth parameters is investigated by correlative analytical microscopy. The latter combines electron microscopy based imaging, Kelvin probe force microscopy, and atom probe tomography. Alkali treatments lead to copper depletion and consequent sharpening of the compositional profiles, and the measured electric potential differences of exposed Cu(In1–x, Gax )Se2 surfaces. Measurable differences in resistivity and potential have also been observed, which are expected to relate to the improved open‐circuit voltage, fill‐factor, and device efficiency. This study frames one perspective as to why post‐deposition alkaline treatments lead to copper depletion, a mildly n‐type semiconductor interface, and higher efficiency for a Cu(In, Ga)Se2 thin‐film photovoltaic device. Abstract : To extend the understanding of alkaline treatments, it is shown that these treatments are responsible for differences in surface chemistry, a feature of Cu(In1–x Gax )Se2 (CIGS). It is observed that the CIGS/CdS heterojunction is affected by the treatment and the differences in copper enrichment are pronounced. This finding demonstrates how leading alkali chemical treatments can have dramatic effects on CIGS.